Crusted Scabies, a Neglected Tropical Disease: Case Series and Literature Review - Nurdjannah Jane Niode; Aryani Adji; Shienty Gazpers; Renate Tamara Kandou; Herry Pandaleke; Dwi Martina Trisnowati; Christy Tumbelaka; Elrovita Donata; Fauziyyah Nurani Djaafara; Hendrix Indra Kusuma; Ali A. Rabaan; Mohammed Garout; et al. (Infectious Disease Reports, 2022)
Crusted scabies is a rare form of scabies that presents with more severe symptoms than those of classic scabies. It is characterized by large crusted lesions, extensive scales, thick hyperkeratosis, and contains a large number of highly contagious itch mites. Crusted scabies is more prevalent in immunocompromised, malnourished, and disabled individuals. This disease has been linked to a variety of health problems, including delayed diagnosis, infection risk, and high mortality, mainly from sepsis, and it has the potential to cause an outbreak due to its hyper-infestation, which makes it highly infectious. This article reports three cases of crusted scabies in North Sulawesi, Indonesia. Recent updates and a comprehensive review of the literature on the disease are also included, emphasizing the critical importance of early diagnosis and effective medical management of patients, which are necessary to prevent the complications and spread in communities.